The Effect of Moodle LMS on Distance Learning Undergraduates’ Performance in Environmental Education - Mohammed , Ibrahim Abba; Ekpo, Charles George; Olatunde-Aiyedun, Tope Gloria; Zakari, Ahmad Yahaya; Ogar, Syvanus Innocent (Yayasan Nurul Yakin Bunga Tanjung, 2025)
The research examined the impact of Moodle on the academic performance and satisfaction of distance learning undergraduates in Environmental Education. A repeated measures design was employed, involving 113 purposefully selected environmental education students. Data were collected using the Environmental Education Achievement Test (EEAT) and the Moodle Online Learning Satisfaction Inventory (MOLSI), both of which underwent validation and reliability testing. Students completed two pre-tests and pre-satisfaction assessments before the intervention, followed by two post-tests and post-satisfaction assessments afterward. Data analysis was conducted using repeated measures analysis of variance. The results indicate that Moodle significantly enhanced students' academic performance (F (3,336) = 193.189, P = 0.00, effect size = 0.963) and satisfaction (F (3,336) = 154.112, P = 0.00, effect size = 0.957). Additionally, Mauchly’s test of sphericity showed no violations for either achievement (W = 0.741, P = 0.621) or satisfaction (W = 0.604, P = 0.572). The study also found that variables such as age, gender, location, and device type did not significantly moderate the impact of Moodle on students' achievement. These findings suggest that incorporating Moodle into distance learning curricula could benefit environmental education lecturers, researchers, and policymakers in Nigeria by fostering the development of skilled and environmentally literate graduates